Luminescence Lifetime-Based Water Conductivity Sensing Using a Cationic Dextran-Supported Ru(II) Polypyridyl Complex - Knöbl, Ya Jie; Johnston, Lauren M.; Quílez-Alburquerque, José; Orellana, Guillermo (Sensors (Basel, Switzerland), 2025)
Water conductivity sensing relies universally on electrical measurements, which are subject to corrosion of the electrodes and subsequent signal drift in prolonged in situ uses. Furthermore, they cannot provide contactless sensing or remote readout. To this end, a novel device for water conductivity monitoring has been developed by employing a microenvironment-sensitive ruthenium complex, [Ru(2,2′-bipyridine-4,4′-disulfonato)3]4−, embedded into a quaternary ammonium functionalized cross-linked polymer support. The degree of swelling of the latter, which leads to a change in the emission lifetime, depends on the water conductivity. The sensor displays a reversible response (2 min ≤ t90 ≤ 3 min) and has been shown to be stable for >65 h of continuous monitoring of 0.8–12.8 mS cm−1 KCl solutions. Changes to the cation do not affect the sensor response, while changes to the anion type induce small effects. Variations in the dissolved O2 or temperature require corrections of the response. The sensor can be interrogated alongside dissolved O2 and pH luminescent sensors based on the same family of indicator dyes to exploit the definite advantages of luminescence lifetime-based detection.